L’iconographie de la croix sur les sarcophages du haut Moyen Âge en Gaule - Anne Flammin (Les Cahiers de l'École du Louvre)
In early Christian art, the image of the cross only began appearing on sarcophagi or in the monumental decoration of Roman churches in the mid-fourth century. After having been considered a sign of infamy, it became a symbol of victory, a “trophy cross” during the reign of Emperor Constantine. In the fifth century, the instrument of torture was clearly represented and often covered with a splendid decoration of precious stones. In the Early Middle Ages, it continued to occupy a predominant place in iconography and was one of the most popular motifs in the decoration of sarcophagi from the late fifth to the early eighth century in Gaul. It is sculpted alone or as part of more complex compositions on the coffins or lids. In order to understand the choices that governed the elaboration of the various compositions of the cross depicted on these tombs, it is necessary to refer to the formulas proposed in the iconography of the Constantinian period. The study of the crosses on Merovingian sarcophagi will make it possible to highlight the legacy of the models of Late Antiquity and the contribution of the Merovingian patrons themselves.